Socialization of Learning Media Maritime English Textbook for Ratings Forming - Achmad Ali Mashartanto; Wibisana Pranata; Riyadi, Slamet; Asta Patma Nugraha, Markus; Siska, Syafni Yelvi (International Journal of Community Service Learning, 2024)
This community service was motivated by several problems in the partners, namely the teaching and learning process of Maritime English Subjects is not optimal because there is no textbooks that can be used by teachers and students. In addition, schools need enrichment in terms of learning media to increase students' enthusiasm for independent learning. This community service aimed to provide solutions to teachers and students through the Maritime English for Ratings Forming learning media. The method used is by socializing the use of Maritime English for Ratings Forming learning media. The subjects of the community service were teachers and students. The data collection method used interview or discussion session with the participants. The instrumentation used interview guidelines. The data analysis used three stages namely data reduction, data presentation, and conclusion. The results of this community service prove that the Maritime English for Ratings Forming textbook can be used by teachers as teaching media, while it can be used by students as learning media. Students will get used to learn independently, because there are guidelines in the textbook that are suitable with the learning curriculum objectives. Students' maritime English knowledge and skills will increase with the availability of learning resources. The school's need for learning media enrichment can be met. The Maritime English for Ratings Forming textbook is one of the maritime English learning media that can be given to each student.